(3cja JSJKeQ HShb GdCSge? (B:s (3MGdI SdWfI YeGf (B/s - (3ebGHdI, Sgjds ((3YeGf(B: s (3OGQ GdQGjI ddfTQ hGdJhRjY(B, s, 2013)
(3GdEbJUGO hGdCShGb GdeGdjI(B- (3CShGb GdGhQGb GdeGdjI(B- (3JWhQ hgjcd bWGY Shb QCS GdeGd aS SdWfI YeGf(B- (3GdChQGb GdeGdjI aj GdHhQUGJ(B- (3eHGOF GdESJKeGQ HGdChQGb GdeGdjI(B- (3GdeMGaX GdESJKeGQjI eDTQGJ GdCShGb(B- (3eNGWQ GdESJKeGQ HGdChQGb GdeGdjI(B- (3JMdjd GdChQGb GdeGdjI(B- (3GdeDTQGJ GdeGdjI GdQFjSjI GdeSJNOeI aj Jbjje GdGSge(B- (3GdeSJKeQ GdLOjO(B- (3GdGReI GdeGdjI GdYGdejI hBKGQgG Ydi GdOhd GdYQHjIs
(3GdedGMb U(B316(3; GdeQGLY U(B297s
Keywords: (3GdESJKeGQs; (3GdGSge GdeGdjIs; (3GdEbJUGOs